The Effect of Relative Corneal Refractive Power Shift Distribution on Axial Length Growth in Myopic Children Undergoing Orthokeratology Treatment - Yang, Xiaoyan; Bi, Hua; Li, Lihua; Li, Shumao; Chen, Song; Zhang, Bin; Wang, Yan (Current eye research, 2021)
To quantify the spatial distribution of relative corneal refractive power shift (RCRPS) to investigate its association with axial length growth. Eighty myopic children were randomly assigned for fitting with type A or B lenses. Axial lengths and corneal topographies were measured at baseline and the 1-, 6-, and 12-months follow-up visits. Treatment-zone decentrations and sizes were derived from tangential maps. RCRPSs were computed by taking the difference between after-treatment and baseline axial maps and then subtracting the apex value. Values at the same radius were averaged to obtain an RCRPS profile, from which four distributional parameters were extracted: the peak value (Rmax), the location where the profile first reached its half peak (X50), and the powers summed within 4- and 8-mm diameter areas (Sum4 and Sum8, respectively). Linear mixed models were used to analyse the correlation between the AL growth and the distributional parameters. At baseline, no significant differences were observed between the two groups. After treatment, Axial length growth was significantly smaller in subjects fitted with type-B lenses (0.15 ± 0.16 vs 0.25 ± 0.22 mm, P = .028). Smaller treatment-zones (1.56 ± 0.14 vs 1.75 ± 0.13 mm, P < .01), smaller X50 values (1.56 ± 0.39 vs 1.98 ± 0.28 mm, P < .01), and greater Sum4 values (11.83 ± 6.47 vs 8.14 ± 5.06 D, P = .01) were also observed in subjects wearing type-B lenses. Among the distributional parameters, only X50 was significantly associated with AL growth in the multiple regression analysis (P = .005). The spatial distribution of RCRPS is critical in retarding AL growth, and the ones reaching peak within a shorter distance from the apex may provide better myopia control.